Celebrating IPPTN’s 10 Years of excellence and achievements: Views of past directors. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2007)
2007 marks IPPTN’s 10th anniversary. This year saw the publication of four books and two research monographs. These numbers are significant to the 22 - personnel institute of which only six are full-time administrative staff. The director, associate research fellows and bulletin editors have full-time day-jobs as professors, associate professors and lecturers in their respective universities. Logistically, a number of them are from Universiti Sains Malaysia.